Evidence that fibrinolytic changes in paediatric obesity translate into a hypofibrinolytic state - Semeraro, Fabrizio; Giordano, Paola; Faienza, Maria F.; Cavallo, Luciano; Semeraro, Nicola; Colucci, Mario (Thrombosis and Haemostasis, 2012)
Paediatric obesity, like adulthood obesity, is associated with an increase of fibrinolysis inhibitors. No study, however, has evaluated the impact of these changes on plasma fibrinolytic capacity. We investigated plasma fibrinolysis and the role therein of the fibrinolytic changes associated with obesity in 59 obese children (body mass index > 95th percentile) and 40 matched controls. Fibrinolysis was investigated by measuring 1) the plasma levels of relevant fibrinolytic factors; 2) the in vitro fibrinolytic capacity under different conditions, using a microplate plasma clot lysis assay; 3) the circulating levels of markers of clotting and fibrinolysis activation. Plasminogen activator inhibitor 1 (PAI-1), total thrombin activatable fibrinolysis inhibitor (TAFI) and fibrinogen levels were higher in obese children as compared to controls (p<0.01). Plasma clots from obese children lysed significantly slower than control clots when exposed to exogenous plasminogen activator, indicating a greater resistance to fibrinolysis. By the use of a selective inhibitor of activated TAFI and by regression analyses we found that fibrinolysis resistance in obese samples was attributable to PAI-1 increase and to enhanced TAFI activation. The ratio between the circulating levels of D-dimer and thrombin-antithrombin complex, a marker of in vivo fibri-nolysis, was significantly lower in obese children, suggesting a reduced fibrinolytic efficiency. These data indicate that paediatric obesity is associated with a hypofibrinolytic state which might contribute to the increased thrombotic risk associated with this condition.
Keywords: Fibrinolytic capacity; PAI-1; TAFI; thrombin; thrombotic risk